2004
DOI: 10.1007/s00442-003-1376-3
|View full text |Cite
|
Sign up to set email alerts
|

The evolution of placental mammal body sizes: evolutionary history, form, and function

Abstract: The unimodal, right-skewed distribution, most frequently identified in contemporary descriptions of placental mammal body size distributions, masks an underlying multidistribution structure; a long-term evolutionary process that has generated a concatenation of two or three frequency distributions specific to locomotory modes (plantigrade, digitigrade and unguligrade). The Afrotropical assemblages are bimodal, with a tendency towards trimodality, whereas the Nearctic assemblage is unimodal. However, mixtures o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
49
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(53 citation statements)
references
References 52 publications
4
49
0
Order By: Relevance
“…Nevertheless, these observations, as well as the observation of comparatively slow MRSs in plantigrade mammals smaller than 1 kg (Lovegrove, 2004), support several hypotheses on the relationship between the evolution of limb morphology and body size in mammals during the Cenozoic (Lovegrove, 2000;Lovegrove, 2001;Lovegrove, 2004;Lovegrove and Haines, 2004;Lovegrove, 2012b;Lovegrove and Mowoe, 2013). For example, the Bowtie model argued that, following the evolution of larger, faster digitigrade carnivores following the Eocene Thermal Maximum, most plantigrade mammals were constrained from evolving to body sizes larger than ~0.5 kg (Lovegrove, 2000;Lovegrove, 2001;Lovegrove and Mowoe, 2013).…”
Section: Maximum Running Speedssupporting
confidence: 63%
“…Nevertheless, these observations, as well as the observation of comparatively slow MRSs in plantigrade mammals smaller than 1 kg (Lovegrove, 2004), support several hypotheses on the relationship between the evolution of limb morphology and body size in mammals during the Cenozoic (Lovegrove, 2000;Lovegrove, 2001;Lovegrove, 2004;Lovegrove and Haines, 2004;Lovegrove, 2012b;Lovegrove and Mowoe, 2013). For example, the Bowtie model argued that, following the evolution of larger, faster digitigrade carnivores following the Eocene Thermal Maximum, most plantigrade mammals were constrained from evolving to body sizes larger than ~0.5 kg (Lovegrove, 2000;Lovegrove, 2001;Lovegrove and Mowoe, 2013).…”
Section: Maximum Running Speedssupporting
confidence: 63%
“…Incorporating vertical ranging data into home range estimates provides a more accurate measure of the distance traveled and energy expended by arboreal primates as well as the density of the resources within their arboreal environment (Milton and May, 1976). Moreover, body size tends to be constrained to moderate sizes in arboreal mammals, such as most of the strepsirhines tested here (Bakker and Kelt, 2000), because of the physical and energetic costs of living in the forest canopy (Lovegrove and Haines, 2004). For example, arboreal taxa must be small enough for tree branches to support their body masses (Emmons, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…The last assumption may be particularly problematic because of primate sexual dimorphism and the annual variations in body size that occur in many Malagasy strepsirhines (Atsalis, 1999;Clutton-Brock, 1985;Ganzhorn and Schmid, 1998;Kappeler, 1991;Leutenegger and Cheverud, 1982;Plavcan and van Schaik, 1997;Smith and Cheverud, 2002). Some researchers have questioned the unimodal, right-skewed distribution that is inherent to the OBS model (Jones and Purvis, 1997;Kozlowski, 1996;Lovegrove and Haines, 2004). Lovegrove and Haines (2004) found that subdividing Afrotropical mammals-including primates-into specific locomotory modes-plantigrade, digitigrade, and unguligrade-resulted in a trimodal rather than unimodal pattern of body size distributions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the most perplexing problems in primate evolutionary biology is understanding the relationship between body size and various ecological variables (Conroy, 2003;Gaston and Blackburn, 1996;Lovegrove and Haines, 2004). Interspecific allometry (IA) in adult body size is often linked to diet, particularly for folivores (Peters, 1986).…”
Section: Introductionmentioning
confidence: 99%